KONTEKSTUALISASI TEORI ‘ÂM DAN KHÂSH DALAM PENEMUAN HUKUM ISLAM DI INDONESIA - Latua, Abidin (Universitas Khairun, 2024)
The discovery of Islamic law in Indonesia faces challenges in integrating classical theories with the local context. This article discusses the contextualization of 'am (general) and khas (specific) theories in the process of discovering Islamic law in Indonesia. This research uses a qualitative approach with literature analysis of classical and modern Islamic legal sources, as well as a study of the practice of implementing Islamic law in Indonesia. The research results show that the 'am and khas theories have high relevance in exploring Islamic law in accordance with the cultural values and needs of Indonesian society. This approach allows flexibility in adapting Islamic law without ignoring sharia principles. Contextualization of this theory is important to bridge the gap between classical texts and dynamic social reality. Thus, this article makes a significant contribution to the development of a methodology for discovering Islamic law that is contextual, progressive, and rooted in the Islamic scientific tradition.